Inclusive Instructional Design for Neurodiverse Learners - Azuka, Chukwuma Victoria; Wei, Calvin Ronchen; Ikechukwu, Unegbu Lasbrey; Nwachukwu, Emmanuel Lucas (MID Publisher International, 2024)
The variations in the cognitive processes through which neurodiverse learners perceive, acquire knowledge, and engage with their surroundings are construed as inherent cognitive diversity, analogous to the biodiversity observed in the natural ecosystem. These variations are a mix of distinctive abilities and difficulties for learners. Consequently, there is a need for interventions aimed at establishing inclusive learning environments through instructional design that will help neurodivergent learners excel in learning environments. Inclusion and equity in education may remain mere statements if it fails to focus on infusing teaching with support and resources to a broad spectrum of learners which includes neurodivergent learners. Neurodiversity refers to the natural variation in human brain function and the resulting differences in how individuals learn, process information, and interact with the world. This spectrum encompasses a wide range of conditions, each with its own unique set of strengths and needs. This paper explores how instructional design can be inclusive and aligned to create a supportive learning environment for neurodiverse learners to foster equity in education. This literature-based approach adopts Vygotsky Social Constructionist Theory, which envision an inclusive model for special learners. The study concludes that by recognizing and accommodating the unique differences of these learners, adopting inclusive instructional design can help unlock the potential of neurodiverse learners and create a more inclusive learning environment.